2022
DOI: 10.1186/s12905-022-02072-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, socio-demographic determinants, and self-reported reasons for hysterectomy and choice of hospitalization in India

Abstract: Background There is limited evidence of hysterectomy in India because of a lack of data in large-scale, nationally representative health surveys. In 2015–16, the fourth National Family Health Survey (NFHS-4)—a cross-sectional survey—collected for the first-time direct information on hysterectomy and self-reported reasons for undergoing the procedure among women in the reproductive age group. The current study evaluates the prevalence, determinants, and choice of hospitalization (Public vs. Priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
1
0
1
Order By: Relevance
“…Here, it is worth noting that the prevalence of hysterectomy has almost doubled in less than a decade which could be a major concern in the future. A recent study conducted using NFHS-5 (2019–2021), estimated the prevalence of hysterectomy to be around 3.3% among women aged 15–49 years which is lower than the present study 19 . A probable reason for this could be the different age groups considered in these studies.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Here, it is worth noting that the prevalence of hysterectomy has almost doubled in less than a decade which could be a major concern in the future. A recent study conducted using NFHS-5 (2019–2021), estimated the prevalence of hysterectomy to be around 3.3% among women aged 15–49 years which is lower than the present study 19 . A probable reason for this could be the different age groups considered in these studies.…”
Section: Discussioncontrasting
confidence: 87%
“…A probable reason for this could be the different age groups considered in these studies. Nonetheless, this study also revealed that the prevalence was highest (9.7%) for women aged 40–49 years 19 . A similar study conducted in China during 2017 reported the prevalence of hysterectomy to be around 7% among women aged 45–54 years which is comparatively lower than our study 20 .…”
Section: Discussionsupporting
confidence: 46%
“…While this was a study in a tertiary hospital in the North-eastern part of Nigeria, our study was in the small private facility in the south-eastern part of Nigeria with different, culture, religion and population demographics. In a study carried out in India across many hospitals, it was found that 3.3% of women of reproductive age had undergone hysterectomy [10]. Even though this value appeared very low compared with our value of 34.5%, their study was limited to women of child bearing age and was also a multi-centre study while ours was a one centre study involving women of all ages.…”
Section: Discussioncontrasting
confidence: 81%
“…Stress plays important role in pathogenesis of uterine fibroids. Greater risk of fibroid development depends on larger count of vital life incidents and stress intensity [36]. The NHS II found a higher uterine leiomyoma prevalence in between women who are long-serving to ill-treat in their early-stages of life.…”
Section: Stressmentioning
confidence: 99%